Gender norms and mass deworming program access in Comé, Benin: A qualitative assessment of gender-associated opportunities and challenges to achieving high mass drug administration coverage. - Rachel E Geyer; Moudachirou Ibikounlé; Mira Emmanuel-Fabula; Amy Roll; Euripide Avokpaho; Abiguel Elijan; Léopold Codjo Wèkè; Comlanvi Innocent Togbevi; Félicien Chabi; Parfait Houngbégnon; Adrian J F Luty; Elodie Yard; et al. (Public Library of Science (PLoS), 2020)
The World Health Organization's Neglected Tropical Disease Roadmap has accelerated progress towards eliminating select neglected tropical diseases (NTDs). This momentum has catalyzed research to determine the feasibility of interrupting transmission of soil-transmitted helminths (STH) using community-wide mass drug administration (MDA). This study aims to identify potential gender-specific facilitators and barriers to accessing and participating in community-wide STH MDA, with the goal of ensuring programs are equitable and maximize the probability of interrupting STH transmission. This research was conducted prior to the launch of community-wide MDA for STH in Comé, Benin. A total of 10 focus group discussions (FGDs) were conducted separately among 40 men, 38 women, and 15 community drug distributors (CDDs). Salient themes included: both men and women believe that community-wide MDA would reduce the financial burden associated with self-treatment, particularly for low income adults. Community members believe MDA should be packaged alongside water, sanitation, and other health services. Women feel past community-wide programs have been disorganized and are concerned these distributions will be similar. Women also expressed interest in increased engagement in the implementation of future community-based public health programs. Men often did not perceive themselves to be at great risk for STH infection and did not express a high demand for treatment. Finally, the barriers discussed by CDDs generally did not align with gender-specific concerns, but rather represented concerns shared by both genders. A door-to-door distribution strategy for STH MDA is preferred by women in this study, as this platform empowers women to participate as health decision makers for their family. In addition, involving women in planning and implementation of community-wide programs may help to increase treatment coverage and compliance.